Impact of anti-TB drugs on modulations of T-cell-receptor-mediated signaling events in TB pleurisy patients - Sharma, Bhawna; Joshi, Beenu; Kumar, Santosh (Frontiers in Immunology, 2025)
Immunity in tuberculosis (TB) infection is complex as Mycobacterium tuberculosis (MTB) is a highly adaptive pathogen and may escape the immune defense through various ways. During MTB infection, immune modulation involves the activation and regulation of various immune cells and signaling pathways to mount an effective defense against the pathogen while minimizing immune pathology. Host pathogen interactions in TB are complex as MTB is a pathogen that is able to adapt and survive and may escape the immune defense through various ways. The limitations of BCG vaccine have energized researchers to identify alternative vaccines for TB. For the rational design of new efficacious and safe vaccines against TB, advanced knowledge of protective and pathological immune responses in TB is needed. It has been well established that the existing anti-TB treatment (ATT) induced an enhanced production of IL-2 and IFN-γ by T cells. This study explores modulations in the activation/phosphorylation of T-cell signaling molecules in the peripheral blood of TBP patients following 6 months of treatment. We reviewed existing evidence on TCR signaling alterations in TB and propose mechanisms by which treatment influences the activation of intracellular calcium mobilization and ZAP-70, PKC-theta, and MAPK activation, which is finally impacting T-cell function by regulating the production of cytokines and impacting the immune control of MTB. Our findings suggest that while treatment reduces bacterial burden, residual immune dysregulation in T-cell activation pathways may persist, influencing long-term T-cell responses. Further studies are needed to fully elucidate these changes and their implications for relapse prevention and therapeutic strategies.